Notes on Productivity - العلي, د.وجيه عبد الرسول (Dirasat in Economics and Business, 1982)
The issue of productivity has captured a great deal of attention in recent years from both researchers and practitioners. This is due to its role in generating real economic growth. At the national level, productivity growth is the best way to stop inflation, improve real income, and make the country more competitive. Are the only way to reduce costs, improve profits, and make the firm more competitive at home and abroad. For individuals, improving productivity is essential for their jobs and standards of living. In this paper an attempt will be made to define and discuss the basic questions related to labor productivity. The emphasis is placed on the importance of raising productivity levels in the Arab World. Ten ways are presented for enhancing labor productivity in the Arab economies. These can be summarized as follows: 1. Continuous research in this field 2. Raising the level of education of workers and eliminating illiteracy. 3. Raising the workers awareness of importance of productivity 4. Applying an effective system of motivation. 5. Making the issue of productivity a national concern. 6. Giving support to vocational education. 7. Developing managerial skills. 8. Circulating knowledge of the latest techniques, ideas and experiences. 9. Raising the level of investment in R&D, education, health and social welfare. 10. Establishing a national center for productivity in each Arab country.